2017
DOI: 10.1002/adem.201700027
|View full text |Cite
|
Sign up to set email alerts
|

A High Strength Ti–SiC Metal Matrix Composite

Abstract: A SiC reinforced Ti-5Al-5Mo-5V-3Cr matrix metal matrix composite was developed. Monolithic blocks of alloy were hot rolled via pack rolling to produce foils for MMC panel fabrication. These were consolidated using hot isostatic pressing and solution treated and aged for optimum strength. The panels exhibited a strength of 2 GPa in tension and 3.5 GPa in compression, compared to the aerospace steel 300M, which has a tensile strength of 1.69 GPa. The fatigue performance of the material exceeded that of MMCs deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…By incorporating commercial engineering ceramic reinforcers such as SiC, TiB, and TiC, a variety of TMCs have been successfully developed and examined to achieve desirable properties at both ambient and elevated temperatures [16][17][18] . Based on the characteristics of reinforcers, the development of TMCs can be categorized into three stages [15,19] : (1) considerable improvement in high-temperature durability such as creep resistance, the strong mechanically anisotropic effect together with the complexity in processing (mostly diffusion bonding technique) dramatically decrease their engineering application potential [20][21][22] In recent years, comparatively more attention has been directed into the investigation of the latter two types of TMCs [23] . Figure 1 | Specific strength versus service temperature for typical structural materials (data excerpted from ref.…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating commercial engineering ceramic reinforcers such as SiC, TiB, and TiC, a variety of TMCs have been successfully developed and examined to achieve desirable properties at both ambient and elevated temperatures [16][17][18] . Based on the characteristics of reinforcers, the development of TMCs can be categorized into three stages [15,19] : (1) considerable improvement in high-temperature durability such as creep resistance, the strong mechanically anisotropic effect together with the complexity in processing (mostly diffusion bonding technique) dramatically decrease their engineering application potential [20][21][22] In recent years, comparatively more attention has been directed into the investigation of the latter two types of TMCs [23] . Figure 1 | Specific strength versus service temperature for typical structural materials (data excerpted from ref.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have confirmed the formation of multiphase intermetallic composites containing TiC x , Ti 5 Si 3 C x , Ti 5 Si 3 , TiSi 2 , and SiC phases, with values of microhardness between 0.6 and 25 GPa for different phases, due to the exposure of mixtures of Ti and SiC at temperatures higher than 600 °C [ 13 ]. This phenomenon serves the useful purpose of increasing the surface wear resistance of built components [ 13 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its wide band gap value, high breakdown electric field, good thermal and electrical conductivity, and high hardness and mechanical strength, SiC can be applied in the electronic (e.g., high power/high frequency devices) or automotive (e.g., brake discs) industry. [1] Silicon carbide is also used as the reinforcement in metal, [2][3][4][5][6][7][8] ceramic, [9,10] or polymer matrix composites. [11,12] SiC addition can improve the thermal or mechanical properties, [13] especially in the case of metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%